Kinetic Adaptations of Myosins for their Diverse Cellular Functions - Heissler, Sarah M. (Traffic, 2016)
Members of the myosin superfamily are involved in all aspects of eukaryotic life. Their function ranges from the transport of organelles and cargos to the generation of membrane tension, and the contraction of muscle. The diversity of physiological functions is remarkable, given that all enzymatically active myosins follow a conserved mechanoenzymatic cycle in which the hydrolysis of ATP to ADP and inorganic phosphate is coupled to either actin-based transport or tethering of actin to defined cellular compartments. Kinetic capacities and limitations of a myosin are determined by the extent to with actin can accelerate the hydrolysis of ATP and the release of the hydrolysis products and are indispensably linked to its physiological tasks. This review focuses on kinetic competencies that – together with structural adaptations – result in myosins with unique mechanoenzymatic properties targeted to their diverse cellular function.